Keep meaning in conversational coordination - Cuffari, Elena C. (Frontiers in Psychology, 2014)
Coordination is a widely employed term across recent quantitative and qualitative approaches to intersubjectivity, particularly approaches that give embodiment and enaction central explanatory roles. With a focus on linguistic and bodily coordination in conversational contexts, I review the operational meaning of coordination in recent empirical research and related theorizing of embodied intersubjectivity. This discussion articulates what must be involved in treating linguistic meaning as dynamic processes of coordination. The coordination approach presents languaging as a set of dynamic self-organizing processes and actions on multiple timescales and across multiple modalities that come about and work in certain domains (those jointly constructed in social, interactive, high-order sense-making). These processes go beyond meaning at the level that is available to first-person experience. I take one crucial consequence of this to be the ubiquitously moral nature of languaging with others. Languaging coordinates experience, among other levels of behavior and event. Ethical effort is called for by the automatic autonomy-influencing forces of languaging as coordination.